1981
DOI: 10.1136/bjo.65.8.549
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind comparison of topical therapy of chlamydial ocular infection (TRIC infection) with rifampicin or chlortetracycline.

Abstract: SUMMARY A double-blind stratified trial was carried out on 85 patients to assess the efficacy of topical therapy with 1 % chlortetracycline eye ointment in comparison with 1 % rifampicin eye ointment in the treatment of chlamydial ocular infection of sexually transmitted origin (paratrachoma). Patients included were selected on the basis of positive culture for Chlamydia trachomatis. A 6-week course of treatment with chlortetracycline or rifampicin 3 times daily gave a clinical cure rate of 80% and 75% and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 3 publications
(2 reference statements)
0
5
0
2
Order By: Relevance
“…This and previous studies indicated that one should not refrain from trying to establish an etiological diagnosis, even if topical treatment with either chloramphenicol or fusidic acid has been given previously (Stenberg et al 1989;). After local tetracycline and erythro-656 mycin therapy chlamydial diagnostic tests may remain positive which is generally in contrast to cases given oral therapy with these two drugs (Darougar et al 1981). As the nasopharynx is also often colonized both in neonatal and adult chlamydial conjunctivitis cases (Schachter et al 1975;Beem & Saxon 1977;Stenberg et al 1988), local treatment is likely to fail.…”
Section: Discussionmentioning
confidence: 99%
“…This and previous studies indicated that one should not refrain from trying to establish an etiological diagnosis, even if topical treatment with either chloramphenicol or fusidic acid has been given previously (Stenberg et al 1989;). After local tetracycline and erythro-656 mycin therapy chlamydial diagnostic tests may remain positive which is generally in contrast to cases given oral therapy with these two drugs (Darougar et al 1981). As the nasopharynx is also often colonized both in neonatal and adult chlamydial conjunctivitis cases (Schachter et al 1975;Beem & Saxon 1977;Stenberg et al 1988), local treatment is likely to fail.…”
Section: Discussionmentioning
confidence: 99%
“…Since the disease is multifocal, systemic antibiotic treatment is favored over topical antibiotics for adult and neonatal chlamydial keratoconjunctivitis [23]. In these disorders, topical antibiotic treatment has been proven ineffective when given alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nach einem Behandlungszeitraum von 6 bzw. 7 Wochen wurde eine Verbesserung der klinischen Symptome, aber keine Erregerelimination erzielt (18,19). Rifampicin kam bisher nicht in der Tiermedizin zum Einsatz.…”
Section: Figunclassified